Estudo da aderência entre aço e concreto em pilares tubulares mistos preenchidos: uma análise experimental e computacional - Bruno Mendes Campolina (2008)
The increasing usage of mixed steel/concrete pillars in Brazil, without the necessary constructive details, is a relevant factor in the study of the adherence between steel and concrete. Many factors, related to the concrete, to the steel tube and to the preparation of the mixed pillars in the construction site, affect the structural technical performance of the pillars. One can find in the literature theoretical and experimental studies covering the subject, but there are scant information concerning the role of the surface of the steel tubes on their adherence to the internal concrete. This role is studied in the present research, employing 36 push-out laboratory experiments and 34 numerical simulations of compression tests. Three cross-section shapes were considered (circular, square and rectangular) and 12 samples, 800 mm long, for each cross-section, were evaluated. Half of the samples had their internal steel surfaces chemically conditioned. The numerical analysis involved three steps: the first involved loading only on the concrete nucleus, the second considered the simultaneous loading of the steel tube and of the concrete nucleus, and finally each of these elements were loaded separately. The experimental and numerical results indicated a significant increase in the steel/concrete adherence after the internal surface conditioning of the steel tubes. The numerical simulations described adequately the experimental results.